2004
DOI: 10.1111/j.1348-0421.2004.tb03551.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Virulence‐Associated Genes in Vibrio mimicus Isolates from Clinical and Environmental Origins

Abstract: The genus Vibrio contains some enteropathogenic species including V. cholerae, V. parahaemolyticus, V. fluvialis and V. mimicus. V. cholerae is responsible for severe cholera epidemics in many parts of the world, especially developing countries (4,12). V. mimicus has been recognized as a biotype of V. cholerae, but was reclassified as an independent species because of differences in some biochemical characteristics including negative sucrose fermentation in 1981 (5). Therefore V. mimicus and V. cholerae are qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
3
40
0
9
Order By: Relevance
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
supporting
confidence: 51%
“…It was also found to be present in V. 74 Vol. 54 BAI et al alginolyticus (Sechi et al, 2000) and V. mimicus (Shinoda and Nakagawa, 2004). In comparison, zot and tcpA did not exist in any of the 30 V. harveyi isolates tested.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…okayama-u.ac.jp of a virulence determinant. For instance, Shinoda et al 5) documented that the gene encoding VMH, but not other toxins, is present in all strains isolated from various clinical and environmental specimens. VMH is secreted from the bacterial cell as an 80-kDa (80399 Da) precursor and, in turn, converted to a 66-kDa (65997 Da) mature form through proteolytic removal of a N-terminal propeptide.…”
Section: Introductionmentioning
confidence: 99%